Diffusion of Social Information in Non-grouping Animals - Tóth, Zoltán; Jaloveczki, Boglárka; Tarján, Gergely (Frontiers in Ecology and Evolution, 2020)
Recent findings indicate that the utilization of social information, produced inadvertently by other individuals through their spatial location and/or interaction with the environment, may be ubiquitous in the animal kingdom. If so, social information-mediated effects on population growth and interspecies interactions may be more prevalent than previously thought. However, little is known about how social information may spread among non-grouping individuals, i.e., in animals that do not form cohesive groups and therefore social attraction among group-mates does not facilitate information diffusion. Are there any perception-related, temporal, and/or spatial parameters that may facilitate or limit the spread of social information in temporary aggregations or among dispersed individuals in a population? We argue that living in cohesive groups is not necessarily required for the diffusion of social information and for social information-mediated effects to emerge in a population. We propose that while learning complex problem-solving techniques socially is less likely to occur in non-grouping animals, the spread of adaptive responses to social stimuli, especially to non-visual cues, can be common and may affect population, and/or community dynamics in a wide range of taxa. We also argue that network-based diffusion analysis could be a suitable analytical method for studying information diffusion in future investigations, providing comparable estimations of social effects on information spread to previous studies on group-living animals. We conclude that more studies are warranted to verify what intrinsic and extrinsic factors influence information propagation among incidentally and/or indirectly interacting individuals if we are to better understand the role of social information in animal populations and how the social and ecological characteristics of species are related to information spread in natural communities.